The Impact of Interactive Teaching Methods on Students’ Learning Outcomes in Blended Learning Environment at Higher Education Institutions - Hoang, Ngoc Tue; Le, Ba Phong (Journal of Posthumanism, 2025)
Due to the importance of teaching methods for critical outcomes of students, this study investigates the effects of interaction teaching methods on student satisfaction and learning outcomes in blended learning environment at Vietnamese higher education institutions. This study used the Structural Equation Modeling to assess the correlation among the latent constructs based on using survey data of 289 students at Vietnamese universities. The findings revealed that three specific dimensions of interactions in terms of student-student, student-instructor and student-content interactions positively affect satisfaction and learning outcomes of students in blended learning environment. Specifically, student-content interaction creates a greater effect on student satisfaction and learning outcomes in comparison with the effects of student-student and student-teacher interactions on student satisfaction and learning outcomes in universities. The paper provides theoretical initiatives on teaching methods that highlight the importance of teaching interaction practices to foster student’s satisfactions and learning outcomes in blended courses in higher educations.